2009
DOI: 10.2134/agronj2009.0125
|View full text |Cite
|
Sign up to set email alerts
|

Nonstructural Carbohydrate Concentrations in Timothy as Affected by N Fertilization, Stage of Development, and Time of Cutting

Abstract: Forages with increased total nonstructural carbohydrate (TNC) concentrations improve the N-use effi ciency of dairy cows. Th is study determined the eff ect of time of cutting (0700 vs. 1500 h), stage of development (heading and anthesis), and N fertilization (30, 50, 70, 90, and 110 kg N ha −1 as NH 4 NO 3 ) on the fermentable carbohydrate concentration of timothy (Phleum pratense L.) grown in northern Ontario, Canada. Forage dry matter (DM) yield and concentrations of N, starch, sucrose, glucose, fructose, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 35 publications
7
19
0
1
Order By: Relevance
“…Fructan is a polymer of fructose and is stored as an energy reserve in many cool-season grasses (Pollock and Cairns 1991), but the standard deviations and ranges of fructan content were small (Table 3). Increasing N fertilization rates did not largely decrease the WSC, mono-and disaccharide or fructan content of timothy genotypes (Table 3), which agreed with the report by Pelletier et al (2009) but disagreed with the reports by Tremblay et al (2005) and Okamoto et al (2011). Hence, selection for WSC content, which is the sum of all these, should provide stable improvement of the fermentation quality of silage at different N fertilizer application levels.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Fructan is a polymer of fructose and is stored as an energy reserve in many cool-season grasses (Pollock and Cairns 1991), but the standard deviations and ranges of fructan content were small (Table 3). Increasing N fertilization rates did not largely decrease the WSC, mono-and disaccharide or fructan content of timothy genotypes (Table 3), which agreed with the report by Pelletier et al (2009) but disagreed with the reports by Tremblay et al (2005) and Okamoto et al (2011). Hence, selection for WSC content, which is the sum of all these, should provide stable improvement of the fermentation quality of silage at different N fertilizer application levels.…”
Section: Discussionsupporting
confidence: 58%
“…Hence, selection for WSC content, which is the sum of all these, should provide stable improvement of the fermentation quality of silage at different N fertilizer application levels. Increasing N fertilization rates did not largely decrease the WSC, mono-and disaccharide or fructan content of timothy genotypes (Table 3), which agreed with the report by Pelletier et al (2009) but disagreed with the reports by Tremblay et al (2005) and Okamoto et al (2011). This conflict seems to come from the N rates used in the studies.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This was subsequently followed by a reduction in fructan concentration from 18 May to 8 July with the exception of Kentucky bluegrass, perennial ryegrass, and Sandberg bluegrass, which exhibited an increase in fructan concentrations from 18 May to 2 June (Table 4). Pelletier et al (2009, 2010) observed increased fructan concentrations in timothy and other grasses from early heading to anthesis and in summer regrowth forage compared to spring growth in grasses. In general, fructan concentration on 3 August continued to decline by the first sampling date of regrowth (15 September) except for perennial ryegrass, orchardgrass, meadow brome, and tall wheatgrass which experienced a 12, 23, 20, and 40% increase in fructan concentrations during that period (Table 4).…”
Section: Resultsmentioning
confidence: 96%
“…This response has been noted previously with respect to WSC (Van Soest, 1982) and more recently in Canada (Tremblay et al, 2005) for timothy ( Phleum pretense L.), especially when forages were harvested during the stem‐elongation or early‐heading stages of growth. In another study (Pelletier et al, 2009), total nonstructural carbohydrates within timothy forages were not affected by N fertilization rate; however, the researchers suggested that this may be explained on the basis of non‐limiting N nutrition. Generally, decreases in WSC in response to N fertilization can be viewed as a net negative with respect to energy density and digestibility.…”
Section: Discussionmentioning
confidence: 92%